Digital Financial Literacy pada Milenial: Pendekatan Knowledge, Attitude dan Behavior (KAB Model) - Normawati, Rani; Santoso, Eko Esti (Jurnal Ilmiah Mahasiswa Manajemen, Bisnis dan Akuntansi (JIMMBA), 2023)
This study aims to determine digital financial literacy among millennials in the Surabaya area. The millennial generation has unique characteristics and is considered very close to technology, especially financial technology, so we are excited to examine millennial behaviour. Evaluation of digital financial literacy is carried out using a knowledge, attitude and behaviour approach, where financial knowledge, digital financial knowledge and financial attitude are determinants of financial behaviour. The research was conducted using a survey method on millennials in the 25-40 age group of 275 respondents. This study uses structural equation modelling (SEM) to estimate the relationship between variables. The analysis of the model shows that financial knowledge, digital financial knowledge and financial attitude affect financial behaviour. As a mediating variable, financial attitude affects it partially, which means the presence or absence of financial attitude, financial knowledge, and digital financial knowledge variables still have a positive and significant influence on financial behaviour